Pathogenesis and diagnosis of myocarditis. Issue 11 (22nd March 2012) - Elamm, Chantal; Fairweather, DeLisa; Cooper, Leslie T
Abstract : Acute myocarditis is an inflammatory disease of the heart muscle that may progress to dilated cardiomyopathy and chronic heart failure. A number of factors including the sex hormone testosterone, components of innate immunity, and profibrotic cytokines have been identified in animal models as important pathogenic mechanisms that increase inflammation and susceptibility to chronic dilated cardiomyopathy. The clinical presentation of acute myocarditis is non-specific and mimics more common causes of heart failure and arrhythmias. Suspected myocarditis is currently confirmed using advanced non-invasive imaging and histopathologic examination of heart tissue. However, the diverse presentations of myocarditis and the lack of widely available, safe, and accurate non-invasive diagnostic tests remain major obstacles to early diagnosis and population based research. Recent advances in the understanding of disease pathogenesis described in this review should lead to more accurate diagnostic algorithms and non-invasive tests.